Pregunta
upstudy study bank question image url

Use the four-step process to find \( f^{\prime}(x) \) and then find \( f^{\prime}(-2), f^{\prime}(3) \), and \( f^{\prime}(7) \). \( f(x)=2 x^{2}+x-1 \) \( f^{\prime}(x)=\square \) \( f^{\prime}(-2)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(3)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(7)=\square \) (Type an integer or a simplified fraction.)

Ask by Potter Pope. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( f^{\prime}(x) = 4x + 1 \) \( f^{\prime}(-2) = -7 \) \( f^{\prime}(3) = 13 \) \( f^{\prime}(7) = 29 \)

Solución

To find the derivative \( f^{\prime}(x) \) of the function \( f(x) = 2x^{2} + x - 1 \) using the four-step process, follow these steps: ### Step 1: State the Function \[ f(x) = 2x^{2} + x - 1 \] ### Step 2: Apply the Power Rule to Each Term The power rule states that if \( f(x) = ax^{n} \), then \( f^{\prime}(x) = a \cdot n \cdot x^{n-1} \). - For the term \( 2x^{2} \): \[ \frac{d}{dx}(2x^{2}) = 2 \cdot 2x^{2-1} = 4x \] - For the term \( x \) (which is \( x^{1} \)): \[ \frac{d}{dx}(x) = 1 \cdot 1x^{1-1} = 1 \] - For the constant term \( -1 \): \[ \frac{d}{dx}(-1) = 0 \] ### Step 3: Combine the Derivatives Add the derivatives of each term to get the derivative of the entire function: \[ f^{\prime}(x) = 4x + 1 \] ### Step 4: Simplify The derivative is already simplified: \[ f^{\prime}(x) = 4x + 1 \] ### Evaluating the Derivative at Specific Points 1. **At \( x = -2 \):** \[ f^{\prime}(-2) = 4(-2) + 1 = -8 + 1 = -7 \] 2. **At \( x = 3 \):** \[ f^{\prime}(3) = 4(3) + 1 = 12 + 1 = 13 \] 3. **At \( x = 7 \):** \[ f^{\prime}(7) = 4(7) + 1 = 28 + 1 = 29 \] ### Final Answers - \( f^{\prime}(x) = 4x + 1 \) - \( f^{\prime}(-2) = -7 \) - \( f^{\prime}(3) = 13 \) - \( f^{\prime}(7) = 29 \)

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Extra Insights

To find \( f^{\prime}(x) \) using the four-step process, we first compute the derivative of \( f(x) = 2x^2 + x - 1 \). 1. **Identify the function**: We have \( f(x) = 2x^2 + x - 1 \). 2. **Apply the power rule**: The derivative of \( x^n \) is \( n x^{n-1} \). Thus: - For \( 2x^2 \), the derivative is \( 2 \cdot 2x^{2-1} = 4x \). - For \( x \), the derivative is \( 1 \). - For \( -1 \), the derivative is \( 0 \). 3. **Combine the results**: Adding these derivatives together, we get: \[ f^{\prime}(x) = 4x + 1. \] 4. **Simplify**: This is already simplified as \( 4x + 1 \). Now, let's find the specific values: 1. **Calculate \( f^{\prime}(-2) \)**: \[ f^{\prime}(-2) = 4(-2) + 1 = -8 + 1 = -7. \] 2. **Calculate \( f^{\prime}(3) \)**: \[ f^{\prime}(3) = 4(3) + 1 = 12 + 1 = 13. \] 3. **Calculate \( f^{\prime}(7) \)**: \[ f^{\prime}(7) = 4(7) + 1 = 28 + 1 = 29. \] Putting everything together, we have: \[ f^{\prime}(x) = 4x + 1 \] \[ f^{\prime}(-2) = -7 \] \[ f^{\prime}(3) = 13 \] \[ f^{\prime}(7) = 29 \]

preguntas relacionadas

Latest Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad